Сатисфакция: сценарий, пьесы и лирика / Евгений Гришковец - Гришковец Евгений Валерьевич (Махаон, 2011)
Экземпляры: СФ-18 (20121119) / Инвентарный номер: 39755z18 / Цена: 226.38 / Сис.шифр: 84(2) / Авт.знак: Г 85 / ГРНТИ: 17.82 / ББК: 84(2=Рус)